Lower tumor volume is associated with increased benefit from immune checkpoint inhibitors in patients with advanced non‐small‐cell lung cancer. Issue 2 (6th August 2020) - Icht, Oded; Domachevsky, Liran; Groshar, David; Dudnik, Elizabeth; Rotem, Ofer; Allen, Aaron M.; Peled, Nir; Reinhorn, Daniel; Jacobi, Oded; Shochat, Tzippy; Bernstine, Hanna; Zer, Alona
Abstract: Aim: Immune checkpoint inhibitors (ICIs) have revolutionized the treatment for advanced non‐small‐cell lung cancer (NSCLC), yet many patients do not benefit from Programmed cell death protein 1 (PD‐1) axis inhibitors, emphasizing the need for additional markers for better patient selection. Our aim was to evaluate the association between tumor volume and response to ICI. Methods: This retrospective ethically‐approved study included all consecutive patients with advanced NSCLC who were evaluated with a fluorodeoxyglucose‐positron emission tomography scan, prior to the first administration of a single‐agent ICI between 1/2016 and 6/2017. Tumor burden was calculated based on total body metabolic tumor volume and sum of all measurable lesions (SOML). Results: Median SOML was 88 mm, and was inversely and significantly associated with progression‐free survival (PFS) (hazard ratio [HR] 2, CI 1.28‐3.37, P  = .003) and overall survival (OS) (HR 2.36, CI 1.13‐4.94, P  = .02). SOML≤80 mm had a significantly longer PFS compared to patients with a SOML≥80 mm (median PFS 9.7 vs 3.7 months, respectively, HR for progression 2.26, CI 1.1‐4.5, P  = .02). Patients with a SOML≤80 also had longer median OS compared to patients with SOML≥80 (median OS 12 vs 9.8 months, respectively, HR for death 3.1, CI 1.2‐8, P  = .018). Conclusions: Low tumor burden was associated with higher response rates (RR), and better PFS and OS in advanced NSCLC patients treated with ICI. These results may improve the selection of patients for treatment with single‐agent ICI, as opposed to the combination with chemotherapy, which might be more appropriate for patients with high tumor burden. Prospective analysis is warranted.